(3ebGdI aj eYQaI GdCTNGUs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3faQV Cf C H GQJaGY LHd Ch TNU hfQjO Cf fYdeg afbje TNUkG Ydi hLg GdGQV eKd Og s
(3BNQgG (B:s
(3fVQH eGHjf GdGabjf ai GdebjGS fMUd ebOGQ GQJaGY GdTNU GdeWdhH GQJaGYg JeJ GdebGdI HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(3433) s
Keywords: (3GdQjGVjGJs